Epicardial adipose tissue volume in patients with coronary artery disease or non-ischaemic dilated cardiomyopathy: evaluation with cardiac magnetic resonance imaging. Issue 1 (January 2019) - Petrini, M.; Alì, M.; Cannaò, P.M.; Zambelli, D.; Cozzi, A.; Codari, M.; Malavazos, A.E.; Secchi, F.; Sardanelli, F.
Abstract : AIM: To compare the amount of epicardial adipose tissue (EAT) in patients with coronary artery disease (CAD) or non-ischaemic dilated cardiomyopathy (NIDCM) with that in patients with negative cardiac magnetic resonance imaging (CMR). MATERIALS AND METHODS: One hundred and fifty patients (median age 57 years, interquartile range [IQR] 46–66 years) who underwent CMR were evaluated retrospectively: 50 with CAD, 50 with NIDCM, and 50 with negative CMR. For each patient, the EAT mass index (EATMI) to body surface area, end-diastolic volume index (EDVI), end-systolic volume index (ESVI), stroke volume (SV), ejection fraction (EF) for both ventricles, and left ventricle (LV) mass index were estimated. Intra and inter-reader reproducibility was tested in a random subset of 30 patients, 10 for each group. Mann–Whitney U test, Kruskal–Wallis test, Spearman's correlation, and Bland–Altman statistics were used. RESULTS: The EATMI in CAD patients (median 15.7 g/m 2, IQR 8.3–25.7) or in NIDCM patients (15.9 g/m 2, 11.5–18.1) was significantly higher than that in negative CMR patients (9.1 g/m 2, 6–12; p <0.001 both). No significant difference was found between CAD and NIDCM patients ( p =1.000). A correlation between EATMI and LV mass index was found in NIDCM patients ( r =0.455, p =0.002). Intra- and inter-reader reproducibility were up to 80% and 72%, respectively. CONCLUSION: Patients with NIDCM or CAD exhibited an increased EATMI in comparison to negative CMR patients. CMR can be used to estimate EAT with good reproducibility. Highlights: EAT in CAD/NIDCM patients was significantly higher than in negative patients. In NIDCM patients, the EAT was positively correlated with left ventricle mass. EAT volume analysis showed a good intra- and inter-reader reproducibility.